Criminalization of Corruption in Public Services in Government Institutions - Hugo S Franata; Faisal Santiago (Riviera Publishing, 2025)
Weaknesses in a state administration system are a reproach for committing an evil act by taking advantage of a position or position. This research aims to describe the criminalization of corruption in public services in government institutions. We hear news about criminal acts of corruption almost every day, whether those who are caught red-handed (OTT) or those who are criminalized for committing corruption. Both the Government and the DPR have established joint regulations to prevent and prevent criminalization in public services that are transparent, accountable and accountable. Public Service is a pillar of a nation's progress which aims to improve the welfare of the people and is a reflection of good and authoritative good governance. This research uses The Gone theory put forward by Jack Bologne which views that the causes of corruption are opportunities, greed, needs, discovery or exposure. This study uses descriptive and library methods (library data collection) by conducting systematic analysis of all collected data as well as Normative Law, both statutory and conceptual approaches. The criminalization of corruption can be minimized with strict policies in public services by: 1. Using theories about Crime Prevention, such as Situational Crime Prevention. 2. Cultivate bureaucratic services, and always improve the time limits for processing permits, 3. Massively and systematically socialize the dangers of corruption to the public and State Civil Apparatus, 4. Establish an online-based integrated licensing system, 5. Strengthen ethics and morals in governance bureaucracy through good corporate governance,